International finance : a casebook - Desai, Mihir A. (Mihir Arvind), 1968- (Hoboken, N.J. : John Wiley, 2007)
Desai's case studies will help readers to understand international financial market, including the instruments and techniques used in the foreign exchange market, monetary policy and international asset allocation.
Exchange rates, markets, and firms -- Module 1.1. exchange rates and global markets -- Foreign exchange markets and transactions -- Exchange rate policy at the monetary authority of Singapore -- Innocents abroad: currencies and international stock returns -- Module 1.2. exchange rates and firms -- Hedging currency risks at AIFS -- Foreign exchange hedging strategies at General Motors: Transactional and translational exposures -- Foreign exchange hedging strategies at General Motors: Competitive exposures -- Multinational finance -- Module 2.1. financing decisions within the firm -- The refinancing of Shanghai General Motors -- Corporate inversions: Stanley Works and the lure of tax havens -- The continuing transformation of Asahi Glass: implementing EVA -- Module 2.2. valuing cross-border investments -- Valuing a cross-border LBO: bidding on the Yell Group -- Globalizing the cost of capital and capital budgeting at AES -- Dow Chemical's bid for the privatization of PBB in Argentina -- Cross-border financing -- Drilling South: Petrobras evaluates Pecom -- Nestle and Alcon-the value of a listing -- Cross-border listings and depositary receipts -- Tax-motivated film financing at Rexford Studios -- The strategy and sources of motion picture finance -- Institutions and finance -- Module 4.1. finance in weak institutional environments -- Growing up in China: the financing of BabyCare Ltd. -- 18.-13. Czech Mate (A-E) -- Module 4.2. regulatory regimes -- Antitrust regulations in a global setting: the EU investigation of the -- GE/Honeywell merger -- Redesigning sovereign debt restructuring mechanisms.
Includes bibliographical references and index.
Keywords: International finance -- Case studies; International business enterprises -- Finance; Foreign exchange; Financial institutions, International